2014
DOI: 10.1038/bjc.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric head CT scan and subsequent risk of malignancy and benign brain tumour: a nation-wide population-based cohort study

Abstract: Background:To evaluate the possible association between paediatric head computed tomography (CT) examination and increased subsequent risk of malignancy and benign brain tumour.Methods:In the exposed cohort, 24 418 participants under 18 years of age, who underwent head CT examination between 1998 and 2006, were identified from the Taiwan National Health Insurance Research Database (NHIRD). Patients were followed up until a diagnosis of malignant disease or benign brain tumour, withdrawal from the National Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
143
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(157 citation statements)
references
References 25 publications
7
143
1
6
Order By: Relevance
“…14 Since the previously published risk analyses, [3][4][5][6][7][8][9][10][11][12][13][14] additional information on CT exposures and scan reports was collected for the period [2003][2004][2005][2006][2007][2008] in half of the participating hospitals and the follow-up (diagnosis of cancer, vital status) was extended up to 31 December 2010. Available information for scans performed before 1995 was sparse and not included in this report.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Since the previously published risk analyses, [3][4][5][6][7][8][9][10][11][12][13][14] additional information on CT exposures and scan reports was collected for the period [2003][2004][2005][2006][2007][2008] in half of the participating hospitals and the follow-up (diagnosis of cancer, vital status) was extended up to 31 December 2010. Available information for scans performed before 1995 was sparse and not included in this report.…”
Section: Data Collectionmentioning
confidence: 99%
“…Other cohort studies have found comparable results. [4][5][6][7] The interpretation of these results nevertheless requires an understanding of whether the excess risks of later malignancies observed after CT scans were due to the radiation exposure or to the underlying medical condition. 8,9 It is indeed possible that the increased incidence rates observed after receipt of CT scans were, at least in part, attributable to the indication for CT use, whether it was the first symptoms of a tumour, a followup for cancer predisposition or a non-cancer disease associated with an elevated risk of developing cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five epidemiologic studies on cancer following radiation exposure from pediatric computed tomography (CT) scans have shown elevated risks of leukemia and brain tumors (1)(2)(3)(4)(5) and other studies are under way (6,7). These studies are record-linkage cohort studies on large numbers of patients collected from existing databases (health insurances and hospitals) with limited or no information on potential confounding factors, which may bias the radiation-cancer association.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is variability in adherence to best practice clinical guidelines [30][31][32][33][34]. The issue of head CT and cancer risk is debated [35][36][37][38][39][40][41]; parental as well as emergency department providers' understanding of medical radiation exposure and cancer risk can vary [42][43][44][45]. Emergent care involves multiple stakeholders, including the patient and family, primary care physicians; nurses; emergency medicine physicians; trauma, pediatric and neurosurgeons; and the imaging team.…”
Section: Introductionmentioning
confidence: 99%